Effects of sun‐drying on physicochemical characteristics, phenolic composition and in vitro antioxidant activity of dark fig varieties. Issue 5 (21st December 2016) - Bachir Bey, Mostapha; Richard, Gaëtan; Meziant, Leila; Fauconnier, Marie‐Laure; Louaileche, Hayette
Abstract: The aim of this investigation was to study the effects of sun‐drying on some physicochemical parameters, phenolic profiles, and antioxidant activities of three dark fig varieties. Sun‐drying led to a decrease of weight and moisture content, an increase of sugar content, but not affect acidity. HPLC analysis revealed the presence of 22 phenolic compounds (14 phenolic acids and 8 flavonoids), including eight compounds that were detected for the first time. Phenolic acid contents decreased after sun‐drying by about 29%, except cinnamic and gallic acids that were increased. Fresh dark fig contained high levels of flavonoids, particularly cyanidin 3‐rutinoside and quercetin 3‐rutinoside; sun‐drying caused decrease in flavonoid contents by about 86%. There are a lot of antioxidant bioactive components besides the phenolic compounds as studied in this work; therefore, the reduction of phenolic compound content by sun‐drying could mainly contribute to the reduction of antioxidant activity of the dark figs. Practical applications: This work aimed to study the effect of sun‐drying, a widely used method for fig drying, on the physicochemical properties, phenolic profiles and antioxidant activities of three dark figs varieties. The sun‐drying method allows the elaboration of dark dried figs with required moisture, but causes a significant reduction of bioactive compounds content as well as antioxidant activity. Safety measures are needed to reduce this negative effect.